Impact of FinTech on Sustainable Development - Pawłowska, Małgorzata; Staniszewska, Aleksandra; Grzelak, Marcin (Wpływ FinTech na zrównoważony rozwój, 2022)
Since the global financial crisis of 2008, we have observed a very rapid increase in use of digital technologies in the finance and development of FinTech companies, and similarly the impact of climate risk on banking. The aim of the paper was to examine the impact of FinTech on achieving sustainable climate and social goals through innovative financial instruments. FinTech can boost the development of green finance, which addresses environmental protection or climate change and has become an opportunity for industrialised countries to achieve sustainable growth. Finally, this paper presents the positive and negative impact of FinTech on the sustainable growth perspective. To assess the impact of Fintech on sustainable finance, the authors carried out a critical analysis of the latest literature and reports of financial institutions.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 2, s. 49-66
Keywords: banks; new technologies; FinTech; sustainable growth; banki; technologie cyfrowe; zrównoważony rozwój